Food Offerings of Ngesur Tanah Salvation in Belikurip Village, Wonogiri Regency: An Ethnolinguistic Study - Imam Baehaqie (Humaniora, 2020)
The purpose of this study was to describe the cultural significance of food offerings in ngesur tanah salvation in Belikurip Village, Wonogiri, Central Java, Indonesia using an ethnolinguistic approach. In data collection, the researcher employed observation and conversation methods which were then analyzed by the ethnographic method by utilizing the triangular meaning proposed by Lyons (1977). It discovered 10 names of food: (1) tumpeng bathok bolu, (2) tumpeng ungkur-ungkuran, (3) undur-undur, (4) tumpeng gung, (5) tumpeng krumpul, (6) tumpeng marga pakewuh, (7) tumpeng obor, (8) sekul suci, (9) samiran, and (10) jenang sepuh. The essence of the offering is the request for salvation for the departed soul and for the family left behind. The results of this study indicate that the use of language (food names) reflect a cultural phenomenon, namely the religious system of offerings from individuals who believe that the deceased’s spirit remains alive and is fully responsible for his or her actions while living in the world. There also appears to be acculturation with other beliefs and religions.